An a n a l y s i s o f e a r l y m i d d l e s t o n e a g e Oc h r e f r o m o l i e b o o m s p o o r t R o c k S h e l t e r, S o u t h A f r i c a - Culey, Jasmin (My University, 2022)
This study focuses on an analysis of ochre excavated from Olieboomspoort Rock Shelter (OBP), Limpopo, South Africa during the 2018/19 excavations. The MSA deposits from which this assemblage was excavated have been dated to approximately 150 ka. Macro and microscopic analysis was undertaken using established ochre analysis principles in order to investigate possible utilisation. Additionally, elemental analysis was undertaken in the form of semi-quantitative portable X-ray fluorescence in order to investigate geological characteristics. A comparison with the ochre assemblage from the 1954 excavations was also undertaken. The results of these analyses indicate that the most predominant raw material in the recent OBP assemblage is specular hematite (identical to that of the 1954 assemblage), which is unique in that it is exceptionally rare at other sites. Only 3% of pieces are definitely utilised, in contrast to the 14% utilised pieces of the 1954 assemblage. There is a preference for pieces with a red streak in both the utilised and unutilised assemblages, while red-purple and purple streak colours are also common. These results may provide support for the hypothesis that OBP was an accumulation site and possibly part of a wider ochre exchange network. If this hypothesis is correct, then this suggests that complex cognitive developments could have taken place even earlier than is commonly suggested (100 ka), around approximately 190-130 ka.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science to the Faculty of Science, School of Geography, Archaeology and Environmental Studies, University of the Witwatersrand, Johannesburg, 2022